Adolescent patellar instability: current concepts review. (February 2017) - Clark, D.; Metcalfe, A.; Wogan, C.; Mandalia, V.; Eldridge, J.
Abstract : Patellar instability most frequently presents during adolescence. Congenital and infantile dislocation of the patella is a distinct entity from adolescent instability and measurable abnormalities may be present at birth. In the normal patellofemoral joint an increase in quadriceps angle and patellar height are matched by an increase in trochlear depth as the joint matures. Adolescent instability may herald a lifelong condition leading to chronic disability and arthritis. Restoring normal anatomy by trochleoplasty, tibial tubercle transfer or medial patellofemoral ligament (MPFL) reconstruction in the young adult prevents further instability. Although these techniques are proven in the young adult, they may cause growth arrest and deformity where the physis is open. A vigorous non-operative strategy may permit delay of surgery until growth is complete. Where non-operative treatment has failed a modified MPFL reconstruction may be performed to maintain stability until physeal closure permits anatomical reconstruction. If significant growth remains an extraosseous reconstruction of the MPFL may impart the lowest risk to the physis. If minor growth remains image intensifier guided placement of femoral intraosseous fixation may impart a small, but acceptable, risk to the physis. This paper presents and discusses the literature relating to adolescent instability and provides a framework for management of these patients. Cite this article: Bone Joint J 2017;99-B:159–70.